CASE STUDY ON THE IMPROVEMENT OF ADULT PROBLEM-SOLVING SKILLS - Vintere, Anna; Čerņajeva, Sarmīte (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2019)
A number of research studies have been done on knowledge, skills and competences in relation to sustainable development. The concept of competences is seen as an essential landmark for orienting teaching and learning for sustainable development of society. One of the most common competencies mentioned in the surveyed literature and most often required by employers is problem solving. To develop an adult needs oriented education program to improve problem-solving skills, the aim of this study is to identify skills and competencies which are necessary for adults to manage their professional life and to overcome challenges of modern world as well as to improve their personal resilience. This study includes two parts. In the first phase of the study, a survey of adult education providers was compiled in four countries: Latvia, Sweden, Italy and Bulgaria. Summarizing the opinions, the main groups of adult problems were identified: family problems, work and career related problems, and so-called general problems (including problems related to decision making), as well as identified problem solving methods. This study summarizes also adult learners survey results in Latvia on problem-solving skills and the needs and opportunities for developing this competence are analysed in details.